Pengaruh Literasi Keuangan, Gaya Hidup, dan Kepercayaan Terhadap Minat Penggunaan Pinjaman Online Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta Tahun 2021 - Gindra Cahayana; Erika Takidah; Achmad Fauzi (Indo Publishing, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and trust on the interest in using online loans for students of the Faculty of Economics and Business, Universitas Negeri Jakarta in 2021, using a quantitative approach with a survey method. The sample was determined through proportional random sampling, resulting in 172 student respondents, while data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was preceded by classical assumption tests, including normality and linearity tests, as prerequisites for further analysis, and subsequently continued with multiple linear regression analysis. Hypothesis testing was conducted using the t-test to examine partial effects, the F-test to examine simultaneous effects, and the coefficient of determination to measure the contribution of independent variables to the dependent variable. The results indicate that financial literacy does not have a significant effect on students’ intention to use online loans, whereas lifestyle and trust have a positive and significant effect. Nevertheless, simultaneously, financial literacy, lifestyle, and trust have a significant effect on students’ intention to use online loans. These findings indicate that students’ intention is more dominantly influenced by lifestyle and the level of trust in online loan services, while financial literacy serves as a supporting factor in shaping more rational and responsible financial behavior, particularly in the context of digital financial decision-making among contemporary university students..